Numerical analysis of the thermal bridge formed at the corners of buildings - Nowicki, Tomasz (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
The paper covers two issues. Presented quantitative results of analyses of the thermal bridge can be directly useful in engineering practice, whereas the methodology applied in the research shows that computer methods reach their mature stage of development promoting them to a common tool of civil engineering workshop. The error made while using standard values of thermal bridge parameters was indicated. The proper values of the parameters were calculated. Methodology of calculating the linear heat transfer coefficient using ABAQUS computer code was described.